Teachers’ professional development as predictor of students’ academic achievement in social studies in Ibadan metropolis (2017)
The study investigated the extent to which teachers’ professional development programme (teachers’ pedagogical skills, knowledge of subject matter, and curriculum awareness) predict students’ achievement in Social Studies among junior secondary school students in Ibadan Metropolis. A total of 18 teachers were observed in class while teaching and also responded to the questionnaire while 360 JSS2 students responded in the Social Studies achievement test using multi-stage sampling technique. Six validated instruments were used for the study. Data were analysed using descriptive statistics and inferential statistics. The combination of the independent variables proved to have joint contribution to students’ achievement in Social Studies. Teachers’ knowledge of subject matter is the most influential when it comes to students’ achievement in Social Studies, followed by teacher’s pedagogical skills. However, curriculum awareness did not contribute significantly to the prediction model on students’ academic achievements in Social Studies. From the findings, recommendations were made, such as organisation of regular workshop and seminars by the government and professional bodies (such as Social Studies Association of Nigeria (SOSAN)) for the teacher and The study investigated the extent to which teachers’ professional development programme (teachers’ pedagogical skills, knowledge of subject matter, and curriculum awareness) predict students’ achievement in Social Studies among junior secondary school students in Ibadan Metropolis. A total of 18 teachers were observed in class while teaching and also responded to the questionnaire while 360 JSS2 students responded in the Social Studies achievement test using multi-stage sampling technique. Six validated instruments were used for the study. Data were analysed using descriptive statistics and inferential statistics. The combination of the independent variables proved to have joint contribution to students’ achievement in Social Studies. Teachers’ knowledge of subject matter is the most influential when it comes to students’ achievement in Social Studies, followed by teacher’s pedagogical skills. However, curriculum awareness did not contribute significantly to the prediction model on students’ academic achievements in Social Studies. From the findings, recommendations were made, such as organisation of regular workshop and seminars by the government and professional bodies (such as Social Studies Association of Nigeria (SOSAN)) for the teacher and adequate investment on Continuous Professional Development programmes, among others.